LTDNA evidence on trial - Roberts, Paul (Frontiers Media, 2016)
Adopting the interpretative/hermeneutical method typical of much legal scholarship, this article considers two sets of issues pertaining to LTDNA profiles as evidence in criminal proceedings. The section titled Expert Evidence as Forensic Epistemic Warrant addresses some rather large questions about the epistemic status and probative value of expert testimony in general. It sketches a theoretical model of expert evidence, highlighting five essential criteria: (1) expert competence; (2) disciplinary domain; (3) methodological validity; (4) materiality; and (5) legal admissibility. This generic model of expert authority, highlighting law's fundamentally normative character, applies to all modern forms of criminal adjudication, across Europe and farther afield. The section titled LTDNA Evidence in UK Criminal Trials then examines English and Northern Irish courts' attempts to get to grips with LTDNA evidence in recent cases. Better appreciating the ways in which UK courts have addressed the challenges of LTDNA evidence may offer some insights into parallel developments in other legal systems. Appellate court rulings follow a predictable judicial logic, which might usefully be studied and reflected upon by any forensic scientist or statistician seeking to operate effectively in criminal proceedings. Whilst each legal jurisdiction has its own unique blend of jurisprudence, institutions, cultures and historical traditions, there is considerable scope for comparative analysis and cross-jurisdictional borrowing and instruction. In the spirit of promoting more nuanced and sophisticated international interdisciplinary dialogue, this article examines UK judicial approaches to LTDNA evidence and begins to elucidate their underlying institutional logic. Legal argument and broader policy debates are not confined to considerations of scientific validity, contamination risks and evidential integrity, or associated judgments of legal admissibility or exclusion. They also crucially concern the manner in which LTDNA profiling results are presented and explained to factfinders in criminal trials.